SYSTEMATIC LITERATURE REVIEW: NURSES AND PATIENT SAFETY - Iman Nurjaman; Ina Saparlina (Medic Nutricia : Jurnal Ilmu Kesehatan, 2023)
Background: One of the most important issues in the world is patient safety, especially when patients are in hospitals. The role of nurses as the most dominant health workers in maintaining patient safety in hospitals is very important because they directly meet patients every day. Therefore, it is important to determine the extent of the nurse's role in preventing incidents that threaten patient safety. Aim: This study was to find out the findings of previous research on how nurses maintain patient safety in hospitals. Design: Systematic Literature Review. Method: Is a literature review, using electronic databases from Scopus, Google Scholar, Pubmed, and Grey literature (National Library of Indonesia) with keywords: patient safety, compliance, and implementation of patient safety by nurses. The study met the following criteria: implementation of patient safety carried out by nurses; research design is qualitative or quantitative; quantitative or qualitative methods; and empirical papers published in English or Indonesian between 2018-2023. The collected articles consist of thirteen narratively arranged papers. Results: It found two papers on health policy, two papers on handover, one paper on risk reduction for falls, one paper on the use of surgical safety checklists, three papers on reducing the risk of infection, and four papers on implementing patient safety. This literature review found that nurses have made various innovations to ensure patient safety in hospitals. Conclusion: Patient safety is a major factor in patient satisfaction during their stay in the hospital, and this innovation can be an example for other hospitals to improve the quality of their services.